From Plant Behavior to Plant Intelligence? - Hiernaux, Quentin (éditions Quae, 2023)
Over the past years, controversies about plant intelligence became featured in scientific journals in ecology and plant biology. Mainstream media and educational literature have also taken up the topic. Could plants be intelligent? Could it be true that they talk to each other, assist and defend each other, etc.? What is the scientific truth behind this idea of plant intelligence? Tackling the issue of intelligence in any organism requires us to study and theorize its behavior. Is the behavior of a plant more like the one of a machine? Or more like animal behavior? Or could some of its aspects even be like the human mind? The experimental results are difficult to interpret in a conceptual tradition focused on humans and animals. They entail a controversial -and sometimes unclear - methodological pluralism.